IRRIGATION STRUCTURES CONSTRUCTED ON THE LEFT AND RIGHT BANKS OF THE AMU DARYA RIVER (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the history and structure of irrigation facilities built along the left and right banks of the Amu Darya River. It focuseson ancient canals, ditches, dams, and other hydraulic structures identified through archaeological research. The study highlights the roleof these systems in agricultural development and their significance for ancient civilizations such as Khorezm and Bactria.